Evaluating the status and prospects of blue carbon in Ireland and the North-East Atlantic - Dolliver, Jessica Poppy (Trinity College Dublin. School of Natural Sciences. Discipline of Zoology, 2022)
Since its conception in 2011, the concept of blue carbon has been valuable to focus the field of ecosystem services on carbon sequestration by marine macrophytic communities, which has been historically overlooked. In this thesis, three studies investigate the status and prospects of blue carbon in Ireland and the North-East Atlantic through: A) a direct evaluation of a naturally-occurring Zostera noltei seagrass meadow in Dublin Bay and its potential value for carbon sequestration (Chapter 1); B) A systematic review of the methods used to determine the fate of macroalgal carbon (Chapter 2); And C), a study quantifying the amount of carbon released to the local environment from an experimental Saccharina latissima kelp farm in Strangford Lough, Northern Ireland (Chapter 3). The combination of these three approaches gives both case-specific insight into the status of blue carbon in Ireland and a general overview on the potential for blue carbon sequestration in the North-East Atlantic region.
APPROVED
Keywords: Blue carbon, carbon sequestration, seagrass, ecosystem services, marine macrophytes, Zostera noltei, Saccharina latissima, kelp, macroalgal carbon